The art of bouncing back : find your flow to thrive at work and in life any time you're off your game - Santore, Darleen (McGraw Hill-Ascent Audio, 2023)
Coach Dar has seen a fair share of calamitous situations in her career, from major league players suffering slumps and season-ending injuries to executives floundering and experiencing financial devastation-plus her own setbacks like three strokes and the loss of her parents. As a mental skills coach, Coach Dar specializes in helping the best of the best get up and get going again after suffering setbacks. In The Art of Bouncing Back, she shares these proven strategies and techniques so you can ensure the obstacles and setbacks you face morph into setups for your next success. You'll discover how to pour a strong emotional foundation, accept feedback, connect with your "Why-Power," and create your own bounce-back environment. Every chapter provides a blueprint that helps you learn more about yourself, so you can identify the exact pivot you need to push forward, start reframing your setbacks, and cultivate the strength you need to handle future adversity better. Packed with strategies and exercises to help you achieve the life-changing results her clients see, The Art of Bouncing Back is what you need to see that the adversity in your life can create opportunities from any setback